2012
DOI: 10.1517/14656566.2012.682150
|View full text |Cite
|
Sign up to set email alerts
|

QTc interval prolongation byd-propoxyphene: what about other analgesics?

Abstract: There is a paucity of available information on the QT interval for most analgesics. Of those for which there is a lot of data, only methadone, oxycodone, and LAAM (levo--acetylmethadol) appear to have a known and accepted level of effect on the QT interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…Many attempts have been made to elucidate a relationship between the structure and function for hERG blockers. Despite the many advances, hERG blockers have a lot of structural variation and there is still no clear relationship between the structure and activity of these drugs [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many attempts have been made to elucidate a relationship between the structure and function for hERG blockers. Despite the many advances, hERG blockers have a lot of structural variation and there is still no clear relationship between the structure and activity of these drugs [12].…”
Section: Discussionmentioning
confidence: 99%
“…The main side effects of opioids include nausea, vomiting, constipation, headache, respiratory depression, decreased cardiac output (especially when applied with benzodiazepines), bradycardia, histamine release, heart electrical disturbance and cardiac arrhythmia and so on [7][8][9][10]. Perhaps the most common cardiac side effect of opioids is the prolongation of the QT interval, which can lead to torsades de pointes (TdP), which is a kind of ventricular tachyarrhythmia with the potential of causing sudden death [11][12][13]. The significance of this side effect is such that in recent years, most of the drugs have been restricted or withdrawn from the market due to this side effect [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, it is marketed as the racemic mixture, which may be important because the (+)isomer has been reported to have NMDA antagonist actions (Gorman et al, 1997;Davis and Inturrisi, 1999). Recent studies have also observed that methadone can prolong the QT interval of the (Raffa et al, 2012).…”
Section: Othermentioning
confidence: 98%
“…In vitro findings are consistent with an effect of methadone on the QTc interval (no animal studies of methadone's QT effects could be found). The question of QTc prolongation caused by methadone has recently been reviewed and is summarized below: Methadone significantly inhibits hERG (the human Ether‐à‐go‐go ‐related gene, KCNH2 , that codes for K v 11.1, the alpha subunit of a K + channel). Methadone has high arrhythmogenic potential at serum levels comparable to those attained when used for the treatment of opioid dependence. The S ‐(+) isomer of methadone ( RS ) is a more potent inhibitor of I Kr (delayed‐rectifier potassium current) than is the R ‐(–) isomer. There is a dose–response relationship between QTc changes and methadone serum levels (more serious proarrhythmic responses correlate with higher doses and lower metabolism of the drug). Certain populations appear to be at greater risk, including females, those with cardiac congenital channel abnormalities, hypokalemia, or low magnesium. …”
Section: Methadone: Clinical History and Attributesmentioning
confidence: 99%
“…Pharmacogenetic variations, including metabolic polymorphisms and cytochrome P450 (CYP450) related drug–drug or drug–food interactions, make methadone prescribing challenging . In addition, the corrected QT (QTc) interval prolongation is of concern and is possibly an underreported contributor to methadone‐related morbidity and mortality . Although methadone represents just 2% of all opioids prescribed, about one‐third of all opioid‐related deaths involve methadone (and this might be an underestimate) .…”
Section: Introductionmentioning
confidence: 99%